The Effect of Anthropometry and Physical Activity toward Elementary School Students’ Interest in Learning Sport - Utama, Dimas Duta Putra; Doewis, Muchsin; Ekawati, Febriani Fajar; Riyadi, Slamet (FKIP Universitas Lampung, 2023)
The Effect of Anthropometry and Physical Activities toward Elementary School Students’ Interest in Learning Sports. Objective: The current study aimed to determine the effect of anthropometry and physical activities toward sport learning interest of elementary school students. Methods: The cross-sectional survey research design was applied in this study with 137 elementary students from two Islamic elementary schools in Pringsewu regency, Lampung as research sample. Moreover, descriptive statistics, inferential statistics, and multiple linear regression with product moment correlation coefficient used to analyze and interpret the data. Finding: there was no significant effect of anthropometry toward learning interest (sig > 0.05), however physical activity performed different effect (sig < 0.05). Moreover, a positive and significant effect of anthropometry toward physical activity was found and the combination of both showed the positive effect towards students learning interest. Conclusion: It exist a strong and signification effect of anthropometry and physical activity toward students’ interest in learning sports of elementary school students.Keywords: anthropometry, physical activities, learning interest, elementary school student.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202339